The Contemporary world looking through the lenses of globalization - Bihasa, Carmelo Rico S. (Mandaluyong City Books Atbp. Publishing Corp., 2022)
"This book provides a unique and interesting introduction to the concept of globalization. It provides the students - who are engaged in the study of the contemporary world - with a sound and logical approach in analyzing and understanding the complex nature of globalization..."--Preface.
CHAPTER 1: UNDERSTANDING GLOBALIZATION: What is Globalization? -- Why Study Globalization? -- Perspectives on Globalization -- Approaches to Globalization -- Drivers of Globalization -- Evolution of Globalization -- Dimensions of Globalization -- CHAPTER 2: IDEOLOGICAL DIMENSION OF GLOBALIZATION: What is Ideology -- Elements of Ideology -- Functions of Ideology -- Ideology and Social Imaginary -- Traditional and Modern Ideologies -- Changes in the Ideological Landscape -- Emerging Ideology of Globalism -- Six Core of Globalization -- CHAPTER 3: POLITICAL DIMENSION OF GLOBALIZATION: What is a Nation State? -- Rise and Dominance of Nation-State -- Nation-State in Decline -- Nation-State in the Globalizing World -- Changing Landscape of Global Politics -- Regionalism -- Global Civil Society -- Global Governance -- CHAPTER 4: ECONOMIC DIMENSION OF GLOBALIZATION: Global Economic Order in the Early Years -- Emergence of the New Global Economic Order -- International Trade and Globalization -- International Finance and Globalization -- International Monetary System -- International Economic Institutions -- Global Economic Instability -- Global North and South Divide -- CHAPTER 5: SOCIAL DIMENSION OF GLOBALIZATION: Global Demography -- Global Migration -- Global City -- Globalization and Religion -- Globalization and Gender -- Globalization and Indigenous People -- Globalization and Peace Studies -- CHAPTER 6: ECOLOGICAL DIMENSION OF GLOBALIZATION: Technology and the Environment -- Drivers of Environmental Issues -- Global Environmental Issues -- Global Environmental Organizations -- Global Environmental Agreements -- Tragedy of the Commons -- Sustainable Development -- Global Environmental Partnership -- CHAPTER: TECHNOLOGICAL DIMENSION OF GLOBALIZATION: Technology and Globalization -- Technology and Its Development -- Global Trends in Technology -- Positive Impact of Modern Technologies -- Negative Impact of Modern Technologies -- Media and Globalization -- Internet and Globalization -- Digital Globalization -- CHAPTER 8: TOWARDS A SUSTAINABLE WORLD: Sustainability and Sustainable Development -- Road to Sustainable World -- The Sustainable World.
Includes bibliographical references (pages 233-245) and index.
Keywords: Globalization